Consider a broccoli stalk: How the concept of edibility influences quantification of household food waste. (15th February 2020) - Moreno, Laura C.; Tran, Thao; Potts, Matthew D.
Abstract: Food waste measurement and policy often seek to differentiate between edible food and associated inedible parts, acknowledging different underlying causes for discard and different preferred solutions for waste management. Given the varying views of edibility within and across cultures, there is no widely agreed upon or universal categorization. To understand how edibility influences the outcome of food waste quantification, we applied four different categorizations to 489 household kitchen diaries from Denver, CO and New York City, NY. We also compared them to how respondents self-characterized edibility. We found that the percentage of total food discarded considered edible ranged from 52% to 71% and that the top ten lists of most discarded edible foods changed based on the categorization used. We found that edibility does matter when studying household food waste in terms of defining the extent of the problem, identifying hot spots for intervention, and tracking progress over time. Additionally, we found that respondents' perceptions of edibility varied and were not aligned with any of the four categorizations. Our findings suggest that how edibility is defined should be rigorously and transparently considered and that the varied perceptions of edibility may influence what and how interventions to reduce wasted food are designed, targeted, and evaluated. Highlights: Edibility has been categorized in multiple ways in food waste research. Edibility impacts quantification of food waste measurement. Widely used categorizations do not capture many foods targeted by interventions. Transparency and consistency in categorization is critical for effective policy.